Bulgaria : Selected Issues and Statistical Appendix. (IMF Staff Country Reports; Country Report ;, 2000)
The paper assesses key aspects of Bulgaria's competitiveness. The challenge is to stay on course and persist with policies that will maintain and strengthen competitiveness. Implementation of the ambitious reform policy with respect to the pension and health care systems is required. The reasons for and implications of low bank credit to the private sector in Bulgaria, and measures to facilitate prudent credit growth are discussed. The statistical data on the economic indices of Bulgaria are also presented in the paper.